2021
DOI: 10.1080/21655979.2021.1988369
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miR-637 serves as a diagnostic biomarker in patients with carotid artery stenosis and predicts the occurrence of the cerebral ischemic event

Abstract: Dysregulation of miR-637 serves as a diagnostic biomarker in patients with carotid artery stenosis and predicts the occurrence of the cerebral ischemic event

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…In line with this, miR-637 was assessed as a potential biomarker of ICAS and IS occurrence [ 122 ]. The prospective analysis revealed that down-regulation of miR-637 was associated with the degree of ICAS, with a sensitivity of 85.6%, and a specificity of 83.3% for ICAS of at least 50% lumen narrowing [ 122 ].…”
Section: Degree Of Carotid Plaque Patients With Asymptomatic and Symp...mentioning
confidence: 99%
See 3 more Smart Citations
“…In line with this, miR-637 was assessed as a potential biomarker of ICAS and IS occurrence [ 122 ]. The prospective analysis revealed that down-regulation of miR-637 was associated with the degree of ICAS, with a sensitivity of 85.6%, and a specificity of 83.3% for ICAS of at least 50% lumen narrowing [ 122 ].…”
Section: Degree Of Carotid Plaque Patients With Asymptomatic and Symp...mentioning
confidence: 99%
“…In line with this, miR-637 was assessed as a potential biomarker of ICAS and IS occurrence [ 122 ]. The prospective analysis revealed that down-regulation of miR-637 was associated with the degree of ICAS, with a sensitivity of 85.6%, and a specificity of 83.3% for ICAS of at least 50% lumen narrowing [ 122 ]. During the 5 year follow-up, the Kaplan–Meier analysis showed that the lower miR-637 levels were associated with a higher incidence of ICAS-related IS (HR = 0.073, 95% CI = 0.017–0.313, p < 0.001), along with severe ICAS (HR = 0.144, 95% CI = 0.045–0.463, p = 0.001) [ 122 ].…”
Section: Degree Of Carotid Plaque Patients With Asymptomatic and Symp...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Jeong et al (2021) reported miR-33a-5p, miR-33b-5p and miR-148a-3p as candidate biomarkers of CS because they bind directly to ATP binding cassette transporter 1 (ABCA1). Liu et al (2021) showed that miR-28-5p alleviated CS by modulating vascular smooth muscle cell proliferation and migration. Zhang and Liu (2021) found that serum miR-637 was considerably reduced in CS patients, and its downregulation was a potential biomarker for the diagnosis of CS and a valuable predictor of cerebral ischemic events.…”
Section: Introductionmentioning
confidence: 99%